Musicogenic seizures in temporal lobe epilepsy: Case reports based on ictal source localization analysis - Bratu, Ionut-Flavius; Nica, Adriana Elena; Oane, Irina; Daneasa, Andrei; Stoica, Sergiu; Barborica, Andrei; Mindruta, Ioana (Frontiers in Neurology, 2023)
Musicogenic epilepsy is a rare form of reflex epilepsy with several etiologies such as focal cortical dysplasia, autoimmune encephalitis, tumors or unspecific gliosis. Different musicogenic auditory stimuli have been identified: pleasant/unpleasant music or specific musicogenic patterns. In this paper, we report two patients with musicogenic seizures. In the first case, the patient was diagnosed with temporal lobe epilepsy, structural etiology with auditory stimuli consisting of pleasant music. Interictal, ictal video-electroencephalography (video-EEG) and signal analysis using independent component analysis pointed out the right temporal lobe onset extending over the neocortical regions. The patient was operated on and is seizure-free. The second case describes a patient with left temporal lobe epilepsy, autoimmune etiology (GAD-65 antibodies). Video-EEG recordings and independent component analysis highlight a seizure onset over the left temporal lobe epilepsy extending also over the neocortical region. Intravenous immunoglobulins treatment was initiated and the patient is seizure-free. In conclusion, musicogenic seizures may be elicited by various auditory stimuli and have a temporal lobe onset extending over the neocortical region.